2018
DOI: 10.1007/s13258-018-0773-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tissue-specific tumor biomarker using different optimization algorithms

Abstract: Background Identification of differentially expressed genes, i.e., genes whose transcript abundance level differs across different biological or physiological conditions, was indeed a challenging task. However, the inception of transcriptome sequencing (RNA-seq) technology revolutionized the simultaneous measurement of the transcript abundance levels for thousands of genes. Objective In this paper, such next-generation sequencing (NGS) data is used to identify biomarker signatures for several of the most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…Several hallmarked studies indicated that the cellular origin signatures that are expressed in primary tissue are sufficiently retained even after primary cancer cells undergo dedifferentiation and colonization in different tissue types (Ma et al, 2005;Tothill et al, 2005). A recent study compared four different algorithms and indicated that the modeling performance differed between these algorithms when analyzing RNA-Seq data from 4,127 primary tumor tissue samples related to nine cancer types (Bhowmick et al, 2019). Among those, ABC yielded the best results; it had an average precision of 91.16% and an average sensitivity of 96.5% for nine cancer types (Bhowmick et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several hallmarked studies indicated that the cellular origin signatures that are expressed in primary tissue are sufficiently retained even after primary cancer cells undergo dedifferentiation and colonization in different tissue types (Ma et al, 2005;Tothill et al, 2005). A recent study compared four different algorithms and indicated that the modeling performance differed between these algorithms when analyzing RNA-Seq data from 4,127 primary tumor tissue samples related to nine cancer types (Bhowmick et al, 2019). Among those, ABC yielded the best results; it had an average precision of 91.16% and an average sensitivity of 96.5% for nine cancer types (Bhowmick et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Support vector machines (SVMs) based on the recursive feature elimination (RFE) algorithm represent embedded methods used for feature selection and classification modeling based on microarray gene expression data, which mined 11,925 genes to 154 genes with definite biological significance (Xu et al, 2016). More than 20,000 genes were generated from NGS RNA-Seq data in other studies (Bhowmick et al, 2019); this number is almost twice as much as that from microarray gene expression data. Hence, RNA-Seq data from nine cancer types (lung, liver, colon, thyroid, prostate, bladder, kidney, brain, and skin) were analyzed with different algorithms, and Artificial Bee Colony (ABC) yielded better results than Ant Colony Optimization, Differential Evolution, and Particle Swarm Optimization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the said technique fosters stability of the model, as stated in [40] that stability in variable selection technique is similarly significant to the accuracy of the prediction model. The study of [41] also a utilized majority voting scheme.…”
Section: ) Data Collectionmentioning
confidence: 99%